Radiation dose in coronary angiography and intervention: initial results from the establishment of a multi‐centre diagnostic reference level in Queensland public hospitals. Issue 3 (4th August 2014) - Crowhurst, James A.; Whitby, Mark; Thiele, David; Halligan, Toni; Westerink, Adam; Crown, Suzanne; Milne, Jillian
Abstract Introduction Radiation dose to patients undergoing invasive coronary angiography (ICA) is relatively high. Guidelines suggest that a local benchmark or diagnostic reference level (DRL) be established for these procedures. This study sought to create a DRL for ICA procedures in Queensland public hospitals. Methods Data were collected for all Cardiac Catheter Laboratories in Queensland public hospitals. Data were collected for diagnostic coronary angiography (CA) and single‐vessel percutaneous intervention (PCI) procedures. Dose area product (PKA), skin surface entrance dose (KAR), fluoroscopy time (FT), and patient height and weight were collected for 3 months. The DRL was set from the 75th percentile of the PKA. Results 2590 patients were included in the CA group where the median FT was 3.5 min (inter‐quartile range = 2.3–6.1). Median KAR = 581 mGy (374–876). Median PKA = 3908 uGym2 (2489–5865) DRL = 5865 uGym2. 947 patients were included in the PCI group where median FT was 11.2 min (7.7–17.4). Median KAR = 1501 mGy (928–2224). Median PKA = 8736 uGym2 (5449–12, 900) DRL = 12, 900 uGym2. Conclusion This study established a benchmark for radiation dose for diagnostic and interventional coronary angiography in Queensland public facilities.